A new look at second liens - Donghoon Lee; Christopher Mayer; Joseph Tracy (Federal Reserve Bank of New York, 2012)
We use data from credit reports and deed records to better understand the extent to which second liens contributed to the housing crisis by allowing buyers to purchase homes with small down-payments. At the top of the housing market, second liens were quite prevalent: As many as 45 percent of home purchases in coastal markets and bubble locations involved a piggyback second lien. Owner-occupants were more likely to use piggyback second liens than were investors. Second liens in the form of home equity lines of credit (HELOCs) were originated to relatively high-quality borrowers, and originations were declining near the peak of the housing boom. By contrast, characteristics of closed-end second liens (CES) were worse on all these dimensions. Default rates of second liens are generally similar to that of the first lien on the same home, although HELOCs perform better than CES. About 20 to 30 percent of borrowers will continue to pay their second lien for more than a year while remaining seriously delinquent on their first mortgage. By comparison, about 40 percent of credit card borrowers and 70 percent of auto loan borrowers will continue making payments a year after defaulting on their first mortgage. Finally, we show that delinquency rates on second liens, especially HELOCs, have not declined as quickly as those on most other types of credit, raising a potential concern for lenders with large portfolios of second liens on their balance sheets.
Keywords: R51; G21; 330; mortgage; second lien